Pembelajaran Pelatihan Media Pembelajaran Berbasis Multimedia - Sarman; Jupron; Yuda Permadi (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The rapid development of digital technology requires improved competence in utilizing multimedia-based learning media to support more interactive and engaging learning processes. However, many students still have limited knowledge and skills in using multimedia applications as learning tools. This community service program aimed to improve participants' knowledge and practical skills through multimedia-based learning media training at MA Raudlatul Hidayah. The implementation method consisted of preparation, material presentation, demonstrations, hands-on practice, discussions, and evaluation. The results showed that participants gained a better understanding of the basic concepts of multimedia-based learning media, became familiar with various supporting applications, and acquired initial skills in developing simple digital learning media. In addition, participants demonstrated high enthusiasm and active involvement throughout the training activities. This program is expected to enhance participants' digital literacy and encourage the effective, creative, and innovative use of technology to support the learning process.